Rintisan laboratorium literasi sosial berbasis komunitas: Kampus, sekolah, masyarakat, industri - Pratiwi, Poerwanti Hadi; Agustina, Dwi; Setya Dhewantoro, Happri Novriza; Disyacitta, Fikri (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2022)
The initial idea of the need for campuses to collaborate with schools, communities, and industries was due to such rapid social changes, especially during and after the Covid-19 pandemic. The Social Literacy Laboratory is a form of collaboration between various communities that have responsibility, concern, and attention to the growth and development process of children and adolescents through literacy (social) activities, both through formal and/or non-formal education. The objectives of this activity are: exploring cooperation and collaboration between multi-parties to consistently and planned efforts to improve the quality of education and the development of reliable resources, carry out regular and scheduled workshop activities to create a Community-Based Social Literacy Laboratory pilot. The target audience in this activity is the teachers of De Britto High School (Yogyakarta), with the number of participants being 25 high school teachers. Some of the activities that have been carried out are: formulation of problems to be solved (stage 1), planning activities and selecting topics and materials (stage 2), and brainstorming the concept of the Social Literacy Laboratory, mapping/identifying the needs of the Social Literacy Laboratory, and follow-up plans.